2015
DOI: 10.1007/s00415-015-7770-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in diagnosis of atypical polyradiculoneuropathies: report of three cases and review of the literature

Abstract: Neuroimaging is increasingly used in the study of peripheral nerve diseases, and sometimes may have a pivotal role in the diagnostic process. We report on three patients with atypical chronic inflammatory polyradiculoneuropathy (CIDP) in whom magnetic resonance imaging (MRI) and nerve Ultrasound (US) were crucial for a correct diagnostic work-out. A literature review on MRI and US in acquired demyelinating polyneuropathies is also provided. Awareness of the imaging features of CIDP will assist in confirmation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Peculiar US patterns in some demyelinating hereditary neuropathies (diffuse homogeneous increase of CSA in the entire length of the nerves), clearly different from those found in typical CIDP, proved to be useful in our cohort (patients #4, 5) suggesting the correct diagnosis. MRI, in particular MR‐neurography, has also proven to be a useful complementary tool in the diagnostic work‐up of neuropathies, especially in selected patients with atypical findings where a close examination of proximal segments, usually inaccessible to US, is crucial . However, being an expensive and time‐consuming exam, the use of MR‐neurography is still limited in routine clinical practice …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peculiar US patterns in some demyelinating hereditary neuropathies (diffuse homogeneous increase of CSA in the entire length of the nerves), clearly different from those found in typical CIDP, proved to be useful in our cohort (patients #4, 5) suggesting the correct diagnosis. MRI, in particular MR‐neurography, has also proven to be a useful complementary tool in the diagnostic work‐up of neuropathies, especially in selected patients with atypical findings where a close examination of proximal segments, usually inaccessible to US, is crucial . However, being an expensive and time‐consuming exam, the use of MR‐neurography is still limited in routine clinical practice …”
Section: Discussionmentioning
confidence: 99%
“…Transient or lack of benefit from immunomodulatory therapies should lead to consider a hereditary neuropathy. Neuroimaging may be helpful in the diagnostic workup …”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that high‐resolution ultrasound (HRUS) is a sensitive technique to identify patients with MMN and CIDP with characteristic NCS abnormalities . Only a few previous reports in single patients and a retrospective chart review have noted abnormal ultrasound findings in patients without these characteristic NCS findings . Here we describe six patients suspected of an inflammatory neuropathy who lacked electrodiagnostic features of demyelination but had abnormal ultrasound findings.…”
Section: Introductionmentioning
confidence: 90%
“…3D MRN has provided a further valuable tool for the assessment of the symmetry and variations in signal intensity and size along the course of plexuses and nerve trunks in patients with CIDP 71 , and has enabled characterization of some unusual features in patients with atypical CIDP variants. For example, in one study, 3D MRN revealed longitudinal morphological changes from the cervical roots to the nerve trunks of the proximal arm in 88% of patients 72 .…”
Section: Inflammatory and Inherited Neuropathiesmentioning
confidence: 99%